STRATEGI SURIAH DALAM MEMPERTAHANKAN HUBUNGAN DIPLOMASI DENGAN RUSIA PADA MASA BASSAR AL ASSAD 2011-2015 (Syria Strategy in Maintaining Diplomatic Relations with The Russian Federation During Bassar - Erman Utomo Adi (HI 16 UMY 138, 2016)
*138 STRATEGI SURIAH DALAM MEMPERTAHANKAN HUBUNGAN DIPLOMASI DENGAN RUSIA PADA MASA BASSAR AL ASSAD 2011-2015 (Syria Strategy in Maintaining Diplomatic Relations with The Russian Federation During Bassar Al Assad Period 2011-2015)